Abatacept to treat chronic intestinal pseudo-obstruction in five systemic sclerosis patients with a description of the index case. Issue 1 (February 2019) - Vigone, Barbara; Beretta, Lorenzo
Chronic intestinal pseudo-obstruction is a severe complication of systemic sclerosis. Inflammatory neuropathy and immunological alterations have a prominent role in the development of systemic sclerosis–related chronic intestinal pseudo-obstruction and immunomodulation might be beneficial in this context. An accidental observation of a patient with juvenile arthritis and a biopsy-proven diagnosis of autoimmune ganglionitis led us to experiment with a new approach to treat systemic sclerosis–related chronic intestinal pseudo-obstruction. In our arthritis patient, the severity and frequency of recurrent episodes of chronic intestinal pseudo-obstruction and aspiration pneumonia were reduced whenever steroids were used to treat arthritic flares, which dramatically improved with abatacept therapy. A systemic sclerosis patient presented typical chronic intestinal pseudo-obstruction features that were neither controlled by dietary interventions nor by prokinetics and were often complicated by acute episodes (5-year) requiring hospitalization. Increased food tolerance was observed whenever parenteral steroids were used during hospitalization. An adequate long-term control of symptoms was then obtained with the use of intramuscular methylprednisolone 20 mg/day; however, symptoms promptly recurred after tapering. Following this motivating example, immunomodulation with abatacept was started. Symptoms were then well controlled and steroids could be weaned off without further acute episodes of sub-occlusion. We postulate that inflammatory neuropathy resembling myenteric ganglionitis may be suspected in selected systemic sclerosis patients with chronic intestinal pseudo-obstruction features. Immunomodulation with drugs that act on T function and restore the regulatory/effector T cell balance may be beneficial in these subjects. The outcomes of four additional systemic sclerosis patients with severe and refractory symptoms of intestinal pseudo-obstruction successfully treated with abatacept are also presented.